2019
DOI: 10.1016/j.nbd.2019.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Reduced disease severity following therapeutic treatment with angiotensin 1–7 in a mouse model of multiple sclerosis

Abstract: Reduced disease severity following therapeutic treatment with angiotensin 1-7 in a mouse model of multiple sclerosis. Neurobiology of disease, 127, 87-100.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…According to the anti-inflammatory and pro-regenerative effects exerted by the Ang(1-7)-MasR axis, the administration of Ang(1-7) in mice undergoing EAE resulted in attenuated disease manifestation, and it was dependent on MasR signaling. This Ang(1-7)-induced EAE amelioration was correlated with decreased immune infiltration, reduced demyelination, and attenuated axonal loss compared with control mice, suggesting a role of the Ang(1-7)-MasR axis in the recruitment of immune cells into the CNS [101].…”
Section: Interaction Between Ras and Dopaminergic System In Neurogenementioning
confidence: 76%
See 1 more Smart Citation
“…According to the anti-inflammatory and pro-regenerative effects exerted by the Ang(1-7)-MasR axis, the administration of Ang(1-7) in mice undergoing EAE resulted in attenuated disease manifestation, and it was dependent on MasR signaling. This Ang(1-7)-induced EAE amelioration was correlated with decreased immune infiltration, reduced demyelination, and attenuated axonal loss compared with control mice, suggesting a role of the Ang(1-7)-MasR axis in the recruitment of immune cells into the CNS [101].…”
Section: Interaction Between Ras and Dopaminergic System In Neurogenementioning
confidence: 76%
“…According to the anti-inflammatory and pro-regenerative effects exerted by the Ang(1–7)-MasR axis, the administration of Ang(1–7) in mice undergoing EAE resulted in attenuated disease manifestation, and it was dependent on MasR signaling. This Ang(1–7)-induced EAE amelioration was correlated with decreased immune infiltration, reduced demyelination, and attenuated axonal loss compared with control mice, suggesting a role of the Ang(1–7)-MasR axis in the recruitment of immune cells into the CNS [ 101 ]. According to this idea, a previous work demonstrated that MasR signaling in monocytes/macrophages favored inflammatory responses in vivo by increasing monocytes/macrophage migration and infiltration into the spinal cord of EAE mice [ 102 ].…”
Section: Interaction Between Ras and Dopaminergic System In Neurogenementioning
confidence: 99%
“…Increased expression and activation of detrimental components of RAS have been reported in circulation, cerebrospinal fluid (CSF) and brain tissue (especially on lesions) of MS patients [ 13 , 47 , 275 ], while there was a reduction in the protective ACE2 component [ 13 ]. This observed status in MS patients is associated with exacerbating neurological signs [ 259 , 276 , 277 ]. Importantly, the detrimental axis is activated in the early steps of experimental autoimmune encephalomyelitis (EAE), as an animal model of MS, but the protective axis is activated during the end time point of this model [ 278 ].…”
Section: Introductionmentioning
confidence: 99%